Incorporating genetic counseling into the evaluation of pediatric bone marrow failure. Issue 2 (27th September 2021) - Schneider, Kami Wolfe; Suttman, Alexandra; McKinney, Christopher; Giller, Roger; Dollerschell, Kaylee; Nakano, Taizo A.
Abstract: The timely identification of germline genetic causes of pediatric bone marrow failure (BMF) impacts medical screening practices, family counseling, therapeutic decision‐making, and risk of progression to myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). At diagnosis, treatment decisions need to be made quickly to mitigate risks associated with profound cytopenias. As genetic testing options are rapidly evolving, an efficient multi‐disciplinary approach and algorithm, including early involvement of a genetics team, is needed to expedite diagnosis and therapeutic decision‐making. This process aids in the identification of appropriate candidates for molecular genetic testing. We present our single center experience reviewing the implementation of genetic counseling and a diagnostic and therapeutic algorithm used to guide genetic evaluation of pediatric BMF. Disease‐specific next‐generation sequencing (NGS) panels were most often pursued in patients who presented with a clinical phenotype consistent with a known inherited BMF syndrome and when trying to reduce incidental or uninformative results. Broader BMF NGS panels were most often utilized when unable to narrow the suspected etiology to a single disorder. Whole exome sequencing helped with optimizing treatment decision‐making in higher risk children with BMF who required expedited hematopoietic stem cell transplantation. The experience has led to improvements to our process for evaluating patients with BMF.